Die sosiologie en etiek van beroepsrasionalisering - Ferreira, R. (Koers, 1996)
The sociology and the ethics of occupational rationalization Circumstances, both inside and outside an organization, at times compel the need for occupational rationalization. For the employees who experience the adversity of redundancy, occupational rationalization is defined as a dehumanizing labour practice, due to the fact that individuals are denied the opportunity to be employed. Jn this article, the Protestant work ethic is utilized in order to evaluate the moral aspects, justifiability, liability, dysfunctions and nonfunctions of occupational rationalization, as well as the situation of redundancy as experienced by rationalized employees. Furthermore, a sociological analysis, utilizing the perspectives of functionalism, critical conflict and interactionism, is given in order to shed light on the interpretation. This is done as the implementation of occupational rationalization necessarily raises both sociological and ethical questions. Sociologically, occupational rationalization has a distinct influence on all facets of an individual's social existence and relationships. Ethically, occupational rationalization makes an appeal to morality in terms of the inherent notions of a Protestant work ethic in respect to an individual’s love for God, the self and for the neighbour. With regard to the evaluation of occupational rationalization as presented in this article, the aspects of a Protestant work ethic which are raised, and the sociological interpretation of occupational rationalization which is given, this discussion focuses on the ambivalence of rationalization, as well as the future of occupational practice. In conclusion, it is determined that although the practice of occupational rationalization is, at limes, a necessity, this process is experienced by the redundant employee as manifest-dysfunctional, nonfunctional, unethical and in many cases, unjustifiable.